Evaluation of the health literacy level of female fibromyalgia patients and relationship between health literacy level and disease activity - Dilek BÜYÜKŞİRECİ,; Ülkü Nesrin DEMİRSOY, (Archives of Rheumatology, 2021)
Objectives: This study aims to evaluate the health literacy in women with fibromyalgia (FM) and relationship between health literacy and disease activity. Patients and methods: This cross-sectional study included a total of 32 female patients (mean age: 46.2±8.8 years; range, 28 to 62 years) with FM according to the 2016 American College of Rheumatology classification criteria and 27 healthy female controls (mean age: 41.7±12.6 years; range, 24 to 65 years) between May 2020 and July 2020. Demographic and clinical characteristics were recorded. Health literacy levels of the participants were assessed with the Turkish version of European Health Literacy Scale (EHLS-TR), disease activity by Fibromyalgia Impact Questionnaire (FIQ), and pain level with the Numerical Rating Scale (NRS). Results: Age, education, marital status, and residential area were similar between the groups. There was a significant difference in the job and income level between the groups (p=0.004 and p<0.001, respectively). The EHLS-TR scores were significantly lower, in FM group compared to the control group (p=0.006, p<0.001, and p<0.001, respectively). There was a negative correlation between the EHLS-TR scores and age in the FM group (r=-0.499, p<0.001). A positive significant correlation was found between education status, income level, and EHLS-TR scores in the FM group (r=0.416, p<0.05 and r=0.316, p<0.05, respectively). Conclusion: Our study results suggest that healthy literacy level is lower in patients with FM compared to healthy controls. In addition, healthy literacy is associated with age, education status, and income level in this patient population.